2010
DOI: 10.1111/j.1751-1097.2010.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Formation of Silver Nanoparticles on Silica by Photochemical Deposition and Other Means

Abstract: Silver nanoparticles (Ag-NP) on silica were produced in aqueous solution by deposition of silver on colloidal silica in a small cuvette using radiation from a xenon-mercury lamp. Ag-NP were also synthesized on a much larger scale with low-level, long-term visible light irradiation for several months. In both cases, the nanoparticle production was monitored by the appearance of the surface plasmon resonance (SPR) band at around 410 nm. The growth of the nanoparticles was directly related to the time exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is noteworthy that we could obtain Ag NPs in several minutes via the environmentally friendly method. In addition, with longer time and higher temperature, the SPR (surface plasmon resonance) becomes stronger, indicating that the content of Ag NPs becomes higher [32,33]. Furthermore, the prepared colloid containing Ag NPs shown in figure 2 was light yellow and transparent, showing that the Ag NPs were well dispersed without aggregation [17].…”
Section: The Kinetic Study For the Synthesis Of Ag Npsmentioning
confidence: 97%
“…It is noteworthy that we could obtain Ag NPs in several minutes via the environmentally friendly method. In addition, with longer time and higher temperature, the SPR (surface plasmon resonance) becomes stronger, indicating that the content of Ag NPs becomes higher [32,33]. Furthermore, the prepared colloid containing Ag NPs shown in figure 2 was light yellow and transparent, showing that the Ag NPs were well dispersed without aggregation [17].…”
Section: The Kinetic Study For the Synthesis Of Ag Npsmentioning
confidence: 97%
“…The reduction of Ag + to AgNPs by Fe 2+ was later suggested as a green method to prepare AgNP-loaded nanohybrids [35]. The reduction of Ag + to Ag 0 or AgNPs was also observed on surface of granular activated carbon [36], bentonite [37,38], and silica [39,40]. For example, by mixing 25 mL of 30 mmol L −1 AgClO 4 with 10 g Ca-montmorillonite, Ag + could be adsorbed in the interlayer space and on the edges of bentonite by cation exchanged, leading to the uniform distribution of Ag + on atomic scale.…”
Section: /Fementioning
confidence: 99%
“…Scanning electron microscopy (SEM) test revealed that further incubation of the mixture induced the reduction of Ag + to Ag 0 in nano-or micro size [38]. Under light irradiation (Xe-Hg lamp or visible light), reduction of Ag + to AgNPs on colloidal silica was observed and monitored by the appearance of the SPR band at around 410 nm [40]. TEM showed that the size of formed AgNPs were in the range of 10-40 nm.…”
Section: /Fementioning
confidence: 99%